(untitled) (Castilla. Estudios de Literatura, 2013)
This work focuses on Simon Zabell’s artistic reading of Alain Robbe-Grillet’s novel La jalousie in his La jalousie. Exhibition. Besides some picture functioning as illustration, Zabell makes installations that include the novel itself, the paper sheets, and other pictures that make explicit the illegibility as a mark of the novel both in the matter of the love affair or not, as in the matter of other manifestations given in the text.